Płeć a skłonność do korzystania z kredytów bankowych - Stola, Emilia (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
Classic economy sets up rationality of decision of subject without their features of personalities. But domain of the behavioral finance confirms strong interaction has sex on financial decision connected with indebtedness. Research in this range has confirmed that sex, education and level of incomes have effect on decisions related with indebtedness importantly. The main aim of elaborations was follow up the dependence among propensity to indebtedness and sex. This relation based on questionnaires was surveyed of 100 clients of private banking’ segment in one of Warsaw’s bank. Results from conducted analyses of regressions and variances have confirmed that sex statically effects on the level of indebtedness. This results of research from this range also. However reaming variables like education or age were irrelevance. In conclusion, these variables did not have any affect on level of indebtedness.